Epilepsy surgery without invasive EEG: early results of a new program Cirurgia de epilepsia sem EEG invasivo: resultados preliminares de um novo programa - Paulo R. M. de Bittencourt; João C. Araújo; Paulo J. M. Leite; Marlus S. Moro; Edson R. Piana; Marcos C. Sandmann (Arquivos de Neuro-Psiquiatria)
A total of 42 patients were submitted to a clinical, behavioural and neuropsychological evaluation with the objective of eventual surgical treatment of epilepsy refractory to the usual clinical therapies. Prolonged video-EEG monitoring, MRI hippocampal volume measurement, lateralization of speech and memory using the amobarbital (Wada) test were used. Of 18 operated cases, 12 were submitted to temporal lobectomy, with a follow-up of 6-30 months; 8 patients had significant improvement in seizures control; 2 patients had partial improvement in seizure frequency and intensity; 2 patients had no improvement in seizure control. One patient underwent right frontal lobectomy with total remission of seizures and 5 had callosotomy with varying degrees of success. There was no mortality. Morbidity included one subdural hematoma, one transient hemiparesis, one episode of mania, one lobar pneumonia and frequent immediately post-operative muscular tension headaches. These early results indicate good results of temporal lobectomy patients investigated through a non-invasive presurgical evaluation. No total, 42 pacientes foram submetidos a avaliação clínica, comportamental e neuropsicológica com o objetivo de eventual tratamento cirúrgico de epilepsia refratária aos tratamentos clínicos usuais. Monitorização de vídeo-EEG digital prolongado, avaliação do volume hipocampal por RM, lateralização de fala e memória pelo teste do Amobarbital (teste de Wada) foram utilizados. Dos 18 pacientes operados 12 foram submetidos a lobectomia temporal, com seguimento de 6-30 meses (média 17 meses), sendo que 8 encontram-se com melhora significativa do controle de crises, 2 com melhora parcial e em 2 não foi observada mudança substancial na intensidade e frequência de crises. Uma paciente foi submetida a lobectomia frontal direita com remissão total de crises. Cinco pacientes foram submetidos a calosotomia com graus variáveis de sucesso. Não houve mortalidade. A morbidade incluiu um hematoma subdural, uma hemiparesia transitória, um episódio de mania, uma pneumonia lobar e cefaléia tensional muscular frequente no pós-operatório imediato. Estes resultados preliminares indicam uma boa resposta do tratamento cirúrgico de epilepsia em um novo centro, com pacientes selecionados através de monitorização não invasiva.